2015
DOI: 10.1109/jphot.2014.2381636
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Cavity Chromatic Dispersion Impacts on 10-Gb/s Optical OFDM Transmissions Over 25-km Dual-RSOA-Based Self-Seeded PON Systems

Abstract: Owing to the lack of strong physical mechanisms capable of elaborately balancing a large number of longitudinal modes created in a self-seeded passive optical network (PON), the resulting coherent-like optical signals are vulnerable to frequencydependent optical phenomena such as chromatic dispersion (CD). In this paper, based on our recently reported real-time dual-reflective semiconductor optical amplifier (RSOA)-based self-seeded adaptive optical orthogonal frequency-division multiplexing (OOFDM) transmitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…The resulting large number of longitudinal modes induces high relative intensity noise (RIN) dominated by mode beating after detection, which can become the main limiting factor for transmission, notably under the effect of chromatic dispersion [4,5,7].…”
Section: Introductionmentioning
confidence: 99%
“…The resulting large number of longitudinal modes induces high relative intensity noise (RIN) dominated by mode beating after detection, which can become the main limiting factor for transmission, notably under the effect of chromatic dispersion [4,5,7].…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, numerical analysis of SWG is an essential step for a project. In this context, to study the SWG characteristics various methods have been applied, some of them based on FDTD [2,5], Fourier Eigenmode Expansion Method [6], and 2D finite element method (FEM) [7]. In this article, a novel 3D vector FEM for analysis of eigenvalue problems for periodic structures is presented.…”
Section: Introductionmentioning
confidence: 99%
“…The performance of the direct detection optical OFDM transmission degrades with various nonlinear optical effects caused by a chromatic dispersion (CD). It has been reported that the CD entails two main optical phenomena as follows . First, An ISI and inter‐carrier interference (ICI) are generated due to the overlap between two OFDM symbols caused by the CD.…”
Section: Introductionmentioning
confidence: 99%